'Beyond the scope of the possible': art, photography and organisational abjection - Laurie Cohen; Philip Hancock; Melissa Tyler (2006)
This paper reflects on the potential value of art photography as a means of critically interrogating the relationship between organisation and abjection. Inspired by Adorno's (1997) understanding of art as a non-conceptual mode of communication and Kristeva's (1982) concept of the abject, we consider the work of several contemporary photographic artists, who have specifically chosen the subject of work organisations in their images. We do so in an attempt to illustrate our argument that art photography shares a capacity with other art forms to reveal, in an immediate and powerful manner, that which is formally excluded from traditional modes of organisational analysis and those discourses that surround and support it.